Boerhaave's Syndrome Secondary to Migration of Gastrostomy Tube. Issue 6 (November 2013) - Yang, PS; Yeh, CH; Chao, YK
Percutaneous endoscopic gastrostomy is a safe procedure for providing nutrition. Complications associated with tube migration such as duodenal obstruction or pancreatitis have been reported. For the first time, we reported a rare complication of gastrostomy tube migration manifested by Boerhaave's syndrome. (Hong Kong j.emerg.med. 2013;20:400-401)